Monitoring and Safety of Aircraft using Wireless Technology - Ajit Tanaji Borate; Dayanand Jadhav; Aditya Vilas Yendhe; Mahesh Sarjerao Lavande; Prathmesh Balu Patil (International Journal of Satellite Remote Sensing, 2024)
Traditional aircraft sensor networks, burdened by wire complexity and high-power demands, struggle with scalability and real-time data acquisition. This paper proposes Bluetooth Low Energy advertising as a transformative solution, leveraging its lightweight, energy-efficient, and secure nature within tree network architecture. Sensors broadcast data packets picked up by strategically placed gateways, enabling efficient data dissemination through multi-hop relaying. The approach boasts scalability due to minimal hardware and power requirements, leading to extended sensor battery life and reduced aircraft power consumption. Secure data transmission is ensured through encryption and redundancy. Real-time data analysis opens doors for applications like predictive maintenance, optimized flight paths, and enhanced passenger comfort. Challenges remain in standardization and potential interference, but BLE advertising presents a promising avenue for revolutionizing aircraft data communication, paving the way for a future of safer, more efficient, and intelligent flight operations.
Keywords: Aircraft; Bluetooth; avionics; communication; maintenance; networks; predictive; sensor